Human Rights, Vocational High School, Christian Education- Homo Hortensis and Political Philosophy - Munte, Alfonso (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Background information for the study was based on the stereotype that exists in society that engineering majors, particularly those related to mining geology, are responsible for causing natural disasters and hastening the deterioration of the environment due to what is learned in the classroom. Furthermore, the qualitative research method uses an interview approach or technique. The interview involved one of the teachers and students in 3 SMK Negeri Buntok, Central Kalimantan. Before conducting interviews, the researcher surveyed the location first by traveling four hours from Palangka Raya. After that, the researcher recorded the interview with the research subject through audio. The audio was transmitted into the interview transcript. Results of interview transcripts that were close to the research were then classified into factual solids and themes. The closest themes were analyzed through references linked to the results and discussion section. Results showed non-quantifiable narratives through various activities of students and teachers, namely through Cambodia, Alamanda, and Asoka, that although they come from Mining Geology majors, they are also entitled and responsible for the sustainability of the mining environment through official procedures in terms of waste management and nature.